Optimal scheduling method of virtual power plant based on bi level programming. Issue 1 (March 2021) - Dunnan, Liu; Yuan, Gao; Weiye, Wang; Jiahao, Liang
Abstract: Virtual power plant controls various types of flexible loads through information integration to realize efficient utilization of energy, which is an important channel to absorb high proportion of renewable energy. In this paper, an optimal scheduling method of virtual power plant based on bi level fuzzy chance constrained programming is proposed. The bi level chance constrained programming is used to describe the power price incentive strategy and the price response of the virtual power plant. The interactive mechanism between the power grid and the virtual power plant is visually displayed. The example shows that this method can realize the distributed generation and active negative of the virtual power plant The effective scheduling of load.